Validated spectrofluorimetric method for the determination of netilmicin based on its interaction with o‐phthalaldehyde/mercaptoethanol: Evaluation of the method's greenness - Salem AlSalem, Huda; Saad Binkadem, Mona; Talal Al‐Goul, Soha; Obaydo, Reem H.; El Hamd, Mohamed A.; Katamesh, Noha S.; Abdel‐Lateef, Mohamed A. (Luminescence (Chichester, England), 2024)
In this study, netilmicin (NTM) was selectively assessed in its dosage forms after a facile derivatization reaction. The proposed approach was based on the interaction between NTM and o‐phthalaldehyde/2‐mercaptoethanol (Roth's reagent). The reaction product was fluorometrically measured at λemission of 434 nm after λexcitation of 338 nm. All reaction conditions for achieving the optimum fluorescence switch‐on activity were visualized and monitored. Moreover, the method was validated under ICH guidelines, and was linear over the range 30–210 ng/ml after plotting netilmicin concentrations against the corresponding fluorescence intensity values. In addition, the selectivity of the developed method was investigated against either the co‐formulated drug (dexamethasone) or a common ophthalmic drop excipient (benzalkonium chloride) without interference from either of them. Furthermore, the developed method was applied to assay netilmicin in various samples of pharmaceutical eye drops with good recovery. Finally, multicriteria greenness and whiteness metrics were used to evaluate the sustainability, greenness, and whiteness of the approach. The applied tools were the AGREE algorithm, the RGB 12 algorithm, and HEXAGON. Spectrofluorimetric determination of netilmicin based on its interaction with o‐phthalaldehyde/2‐mercaptoethanol.